Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$\displaystyle \int\frac{1+x+\sqrt{1+x^2}}{\sqrt{x+1}+\sqrt{x}}dx$

My solution::

Multiply Numerator and Denominator by $\sqrt{x+1}-\sqrt{x}$

$\displaystyle = \int\left\{1+x+\sqrt{1+x^2}\right\}.\left\{\sqrt{x+1}-\sqrt{x}\right\}dx$

$\displaystyle = \int (1+x)^{\frac{3}{2}}dx-\sqrt{(1+x).(1+x^2)}dx-\int \sqrt{x}.(1+x)dx-\sqrt{x}.\sqrt{1+x^2}dx$

$\displaystyle = \frac{2}{5}(1+x)^{\frac{5}{2}}-I-\frac{2}{3}x^{\frac{3}{2}}-\frac{2}{5}x^{\frac{5}{2}}-J$

where $\displaystyle I = \int (1+x)^{\frac{1}{2}}.(1+x^2)^{\frac{1}{2}}dx$ and $J\displaystyle =\int x^{\frac{1}{2}}.(1+x^2)^{\frac{1}{2}}$

Now My Question How can I solve These $2$ Integrals $I$ and $J$

plz help me.

Thanks

share|improve this question
    
The integrands in $I$ and $J$ are of the form, square root of a cubic. In general, such antiderivatives cannot be expressed in terms of the usual functions of intro calculus, but instead require what are called "elliptic functions". –  Gerry Myerson Jan 20 '13 at 12:18
    
Thanks Gerry Myerson ... would you like to give me an link or document about Elliptical function and how can i solve these type of integral using elliptical function –  juantheron Jan 20 '13 at 17:12
    
I think if you do a websearch on "elliptic integral" or "elliptic function" you will find loads of material is available. You don't so much "solve" the integral using elliptic functions, as define the elliptic functions to be the solutions of this kind of integral. Once you've looked over the literature on the topic, if you have any questions about what you have found, I encourage you to post new questions to m.se. –  Gerry Myerson Jan 20 '13 at 22:29
add comment

2 Answers

up vote 5 down vote accepted

One can be brought to the form $\int u^a (1-u)^b \mathrm{d}u$ which is discussed in this answer of mine: $$\begin{eqnarray} J &=& \int \sqrt{x} \sqrt{1+x^2} \mathrm{d}x \stackrel{u=x^2}{=} \frac{1}{2} \int u^{-1/4} (1+u)^{1/2} \mathrm{d} u \\ &=& \frac{2}{3} u^{3/4} \cdot {}_2F_1\left(-\frac{1}{2}, \frac{3}{4}; \frac{7}{4}; -u\right) +\text{const.} = \frac{2}{3} x^{3/2} \cdot {}_2F_1\left(-\frac{1}{2}, \frac{3}{4}; \frac{7}{4}; -x^2\right) +\text{const.} \end{eqnarray} $$ The other integral is an elliptic integral: $$\begin{eqnarray} I &=& \frac{4}{15} \sqrt{2\alpha} \left(\alpha \operatorname{F}\left( \arcsin \left( \frac{x-\frac{1}{\alpha}}{x+\alpha}\right) ,-\alpha^2\right) -\frac{1}{\alpha} \operatorname{E}\left(\arcsin \left( \frac{x-\frac{1}{\alpha}}{x+\alpha}\right) ,-\alpha^2\right)\right) \\ && + \frac{2}{15} \sqrt{1+x}\sqrt{1+x^2} \left(3x+1 + \frac{4}{x+\alpha}\right) + \text{const.} \end{eqnarray} $$ where $\alpha = \sqrt{2}+1$ and $$ \operatorname{E}\left(\phi, m\right) = \int_0^\phi \sqrt{1-m \sin^2\varphi}\, \mathrm{d}\varphi, \quad \operatorname{F}\left(\phi, m\right) = \int_0^\phi \frac{\mathrm{d}\varphi}{\sqrt{1-m \sin^2\varphi}} $$ It can be evaluated using the Jacobi elliptic functions substitution: $$ \operatorname{sn}\left(t, -\alpha^2\right) = \frac{x-\frac{1}{\alpha}}{x+\alpha} $$ as described in Byrd and Friedman.

share|improve this answer
    
Thanks Gerry Myerson and also Thanks to Sasha. –  juantheron Jan 22 '13 at 3:10
1  
@juantheron : could you please mark this as the answer? –  Arjang Sep 1 '13 at 11:43
    
@Sasha: But why $I$ can express in terms of incomplete elliptic integral of the first kind and incomplete elliptic integral of the second kind as you claimed? –  Harry Peter Sep 14 '13 at 4:29
add comment

For any real number of $x$ ,

When $|x|\leq1$ ,

$J=\int x^\frac{1}{2}(1+x^2)^\frac{1}{2}$

$=\int x^\frac{1}{2}\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{2n}}{4^n(n!)^2(1-2n)}dx$

$=\int\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{2n+\frac{1}{2}}}{4^n(n!)^2(1-2n)}dx$

$=\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{2n+\frac{3}{2}}}{4^n(n!)^2(1-2n)\left(2n+\dfrac{3}{2}\right)}+C$

$=\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{2n+\frac{3}{2}}}{2^{2n-1}(n!)^2(1-2n)(4n+3)}+C$

$I=\int(1+x)^\frac{1}{2}(1+x^2)^\frac{1}{2}$

$=\int(x+1)^\frac{1}{2}\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{2n}}{4^n(n!)^2(1-2n)}dx$

$=\int(x+1)^\frac{1}{2}\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!(x+1-1)^{2n}}{4^n(n!)^2(1-2n)}dx$

$=\int(x+1)^\frac{1}{2}\sum\limits_{n=0}^\infty\sum\limits_{k=0}^{2n}\dfrac{(-1)^{-n}(2n)!C_k^{2n}(-1)^{2n-k}(x+1)^k}{4^n(n!)^2(1-2n)}dx$

$=\int\sum\limits_{n=0}^\infty\sum\limits_{k=0}^{2n}\dfrac{(-1)^{n-k}((2n)!)^2(x+1)^{k+\frac{1}{2}}}{4^n(n!)^2k!(2n-k)!(1-2n)}dx$

$=\sum\limits_{n=0}^\infty\sum\limits_{k=0}^{2n}\dfrac{(-1)^{n-k}((2n)!)^2(x+1)^{k+\frac{3}{2}}}{4^n(n!)^2k!(2n-k)!(1-2n)\left(k+\frac{3}{2}\right)}+C$

$=\sum\limits_{n=0}^\infty\sum\limits_{k=0}^{2n}\dfrac{(-1)^{n-k}((2n)!)^2(x+1)^{k+\frac{3}{2}}}{2^{2n-1}(n!)^2k!(2n-k)!(1-2n)(2k+3)}+C$

When $|x|\geq1$ ,

$J=\int x^\frac{1}{2}(1+x^2)^\frac{1}{2}$

$=\int x^\frac{1}{2}\left(x^2\left(\dfrac{1}{x^2}+1\right)\right)^\frac{1}{2}$

$=\int x^\frac{3}{2}\left(1+\dfrac{1}{x^2}\right)^\frac{1}{2}$

$=\int x^\frac{3}{2}\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{-2n}}{4^n(n!)^2(1-2n)}dx$

$=\int\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{\frac{3}{2}-2n}}{4^n(n!)^2(1-2n)}dx$

$=\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!x^{\frac{5}{2}-2n}}{4^n(n!)^2(1-2n)\left(\dfrac{5}{2}-2n\right)}+C$

$=\sum\limits_{n=0}^\infty\dfrac{(-1)^n(2n)!}{2^{2n-1}(n!)^2(2n-1)(4n-5)x^{2n-\frac{5}{2}}}+C$

share|improve this answer
    
This is not a closed-form expression. –  user64494 Sep 21 '13 at 5:24
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.